SYNTHESIS OF ARYLVINYL ETHER MONOMERS TO OBTAIN POLYMERIC MEMBRANES - Sh. Bahriddinova; M. Soliev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Today, there are many ways to obtain polymer membranes. In particular, part of the production of target materials is the processing of plastic waste, the production of composite, copolymer and other materials using industrial waste generated in the production of polymer products. The article presents the results of a study of the conditions, reactions and yield of aryl vinyl ether synthesis for the production of polymer composite materials with membrane properties.